Raman spectroscopic studies of LixSiy compounds. (29th April 2013) - Gruber, Thomas; Thomas, Daniel; Röder, Christian; Mertens, Florian; Kortus, Jens
<x xml:space="preserve">Abstract</x> The phase diagram of the Li–Si system contains several phases with Li and Si in well defined ratios. So far, only the Raman spectrum of LiSi has been reported. In this work, we present experimental Raman scattering results for the crystalline lithium silicide phases Li12Si7, Li7Si3, Li13Si4, and Li21Si5/Li22Si5, which show clearly distinguishable Raman modes. The experimental results are compared with theoretical data obtained by density functional theory calculations. Copyright © 2013 John Wiley & Sons, Ltd.